PENGARUH PEMBELAJARAN BERBASIS LABORATORIUM TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Elka Ayu Setianingsih; Arwin Achmad; Rini RitaT Marpaung (Universitas Lampung, 2013)
The purpose of this study is to determine the effect of the laboratory-based learning toward student activitites and learning outcomes. The research used a pretest-posttest design. The samples in this study were student of class VIIIA and VIIIB that were randomly selected using cluster random sampling technique. The study collected quantitative data and qualitative data. Quantitative data of student learning outcomes obtained from pre test and posttest. Quantitative data was analyzed using t-test at 5% confidence level. Qualitative data was student activity observed during laboratory-based learning.The results of this study showed that the N-gain score of student of experimental class which using laboratory-based learning was 60.51 higher than the average N-gain score of student of control class which using discussion learning (49.71). Furthermore, the N-gain score of students' learning activities of the experimental class reached 77.4 was higher than the control class that was 70.4. It can be concluded that the use of laboratory-based learning could improved student activities and learning outcomes of human digestive system concepts. Keywords: Lab-Based Learning, Student Activities, Learning Outcomes, Digestive System.